PRODUCTIVE WAQF MANAGEMENT AS A SOURCE OF ISLAMIC EDUCATION FINANCING NON-STATE BUDGET - Yuriyan Dinata Yuriyan; Salfen Hasri; Sohiron (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the process of productive waqf management as a source of Islamic education financing non-state budget in madrasah, as well as to identify the management factors that most determine its success. The study uses a qualitative approach with a library study design, supported by data collection techniques in the form of documentation and observation of productive waqf management practices in madrasah. The results of the study indicate that productive waqf management in madrasah runs through three dominant functions, namely structured planning, the implementation of active agricultural and plantation business units that generate income, and routine supervision that directly involves institutional leaders. These three functions form a management cycle that is capable of making waqf a complementary financing source that gradually reduces madrasah dependence on the state budget. The determining factors for success rest on the consistency of planning and the commitment of leadership supervision, although the limited human resources of nazhir and the not yet productive nature of all waqf assets remain structural obstacles that still need to be addressed. These findings contribute to the achievement of SDG 4 on quality and inclusive education, because the productive waqf-based financing model enables madrasah to independently organize quality education without burdening students or fully relying on state subsidies.